An observational analysis of discontinuation and non-publication of osteoarthritis trials. Issue 9 (September 2018) - Scott, J.; Cooper, C.M.; Checketts, J.X.; Cutler, J.; Boose, M.; Morris, J.; Vassar, M.
Summary: Objective: Discontinuation and nonpublication are causes for concern in highly funded research areas of prevalent medical conditions. The aim of our study is to evaluate the rate of discontinuation and nonpublication in osteoarthritis randomized controlled clinical trials. Design: We used theClinicalTrials.gov advanced search using the keyword "osteoarthritis" for phase 3 or phase 4 clinical trials in adults. Two investigators then independently screened the search results by registered title, condition, study design, and completion date. We then performed a systematic search to determine the publication status of the study. Results: Our final analysis included 273 studies. Our analysis of these studies included 243 (89%) completed and 30 (11%) discontinued trials. A total of 121, 307 (92%) and 10, 368 (8%) patients participated in completed and discontinued trials, respectively. Following our searches of PubMed, Embase, and Google Scholar, we identified 67 of the 243 (27.6%) studies as completed but having not reached publication in manuscript form. Conclusions: If discontinuation and non-publication rates in osteoarthritis trials continue to be sub-optimal, already scarce research resources will continue to be wasted. One possible explanation for the witnessed nonpublication that warrants further investigation is the issue of publication bias or selective reporting bias, two known problems that decrease research productivity and ethics.